2013
DOI: 10.1128/aem.02632-12
|View full text |Cite
|
Sign up to set email alerts
|

Bartonella Infections in Deer Keds (Lipoptena cervi) and Moose (Alces alces) in Norway

Abstract: cInfections with Bartonella spp. have been recognized as emerging zoonotic diseases in humans. Large knowledge gaps exist, however, relating to reservoirs, vectors, and transmission of these bacteria. We describe identification by culture, PCR, and housekeeping gene sequencing of Bartonella spp. in fed, wingless deer keds (Lipoptena cervi), deer ked pupae, and blood samples collected from moose, Alces alces, sampled within the deer ked distribution range in Norway. Direct sequencing from moose blood sampled in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
45
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(48 citation statements)
references
References 40 publications
3
45
0
Order By: Relevance
“…Although we were not able to detect Bartonella in fully developed pupae, it is very likely that L. cervi is a vector for this pathogen. Other studies showed that Bartonella DNA was present in various L. cervi life stages as well [ 8 , 10 , 12 , 13 , 18 ]. In addition, it was reported that another hippoboscid species ( Melophagus ovinus ) is able to transmit Bartonella vertically from females to their offspring [ 13 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Although we were not able to detect Bartonella in fully developed pupae, it is very likely that L. cervi is a vector for this pathogen. Other studies showed that Bartonella DNA was present in various L. cervi life stages as well [ 8 , 10 , 12 , 13 , 18 ]. In addition, it was reported that another hippoboscid species ( Melophagus ovinus ) is able to transmit Bartonella vertically from females to their offspring [ 13 ].…”
Section: Resultsmentioning
confidence: 99%
“…In general, L. cervi is considered a mere nuisance for animals only [ 9 ], and clinical symptoms after they bite humans are not very severe [ 10 , 11 ]. However, L. cervi is also considered a potential vector for a number of zoonotic pathogens, such as Bartonella , Anaplasma , and Rickettsia species [ 12 - 14 ]. Lipoptena cervi shows a number of interesting life history traits, in which vertical transmission of pathogens from females to offspring seems to be essential to facilitate efficient transmission between vertebrate hosts.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study isolated Bartonella spp. in both deer keds and moose blood [47], indicating that moose most likely represents a reservoir of infection and that keds acts as a vector for spread of infection with Bartonella spp. Further, a recent epizootic of alopecia in moose was associated with massive deer ked infestation [9] and the probable harassment for domestic animals should not be neglected.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it suggests that Bartonella and haemoplasma species detected in S. caffer in the present study may be potentially transmitted by these tick species. In addition to possible role of ticks in the transmission of Bartonella, several studies have reported the isolation or molecular detection of Bartonella species in other bloodsucking arthropods associated with wild and domestic ruminants (Chung et al, 2004;Dehio et al, 2004;Halos et al, 2004;Duodu et al, 2013;Gutiérrez et al, 2014). Regarding the haemoplasma transmission, few studies have accessed the mechanisms of transmission by arthropod vectors.…”
Section: Discussionmentioning
confidence: 99%